Psoas abscess due to mycobacterium tuberculosis: a case report - Khorgade, Ranjana R.; Bhise, Pramod R.; Deshmukh, Mukta M. (International Journal of Research in Medical Sciences, 2017)
Iliopsoas abscess (IPA), a collection of pus in the iliopsoas compartment that has traditionally been classified into primary and secondary according to its origin, is an infrequent condition worldwide. Mostly active TB is confined to the lung, but approximately 15% are extrapulmonary. The most common types of extrapulmonary TB are, in descending order of frequency, pleural, lymphatic, bone and joint, genitourinary, miliary disease, meningitis, and peritonitis. Tuberculosis (TB) remains as one of the leading opportunistic infection in patients in developing countries. Here we report a rare case of psoas abscess of tubercular origin in patient who presented with back pain and limping. Diagnosis is done based on history, physical examination, plain radiology, microbiological investigation and CT scan of abdomen which revealed a large psoas abscess caused by M. tuberculosis. Patient was diagnosed as psoas abscess due to Mycobacterium tuberculosis and treated empirically with DOTS category I and significant functional improvement was noted on follow up.